Analysis of Work Discipline and Work Environment on Employee Job Satisfaction at PDAM Tirtanadi Sisingamangaraja Medan - Nuraini kemalasari Istiqomah; Dian Yulis Wulandari; Ghina Taqyyah Harahap (International Journal of Management, Economic and Accounting, 2023)
The purpose of this study is to find out the influence of work discipline on employee job satisfaction, to find out the influence of work environment on employee job satisfaction and to find out the influence of work discipline and work environment on employee job satisfaction at PDAM Tirtanadi Sisingamangaraja Medan. The approach used in this study is an associative approach. The population in this study is all employees at PDAM Tirtanadi Sisingamangaraja Medan which totals 272 people and the sample used in this study is using a sampling technique using the slovin formula so that the sample in this study is 73 employees. The data collection technique in this writing uses a questionnaire. The data analysis techniques in this paper use the Data Quality Test, Classical Assumption Test, Multiple Linear Regression, and Hypothesis Test. The data processing in this study uses the SPSS v. 26 software program. It is partially known that work discipline has a positive and significant influence on employee job satisfaction at PDAM Tirtanadi Sisingamangaraja Medan because it has a sig. 0.004 < 0.05 and 3,408 > 1,666. It is partially known that the work environment has a positive and significant influence on employee job satisfaction at PDAM Tirtanadi Sisingamangaraja Medan because it has a sig. 0.003 < 0.05 and 2.562 > 1.666. It is simultaneously known that work discipline and work environment have a positive and significant influence on employee job satisfaction at PDAM Tirtanadi Sisingamangaraja Medan. This study has an R Square value of 0.587, meaning that the variation of the independent variable is 46.1%, while the remaining 53.9% is explained by other variables that are not included in the regression model in this study.